Old Yeasts New Questions - Lucas, Candida; Pais, Celia (IntechOpen, 2017)
Yeast-based biotechnology traditionally regards the empirical production of fermented drinks and leavened bread, processes which surprisingly keep posing challenges and fuelling research. But yeasts nowadays also provide amenable cell factories, producing bulk and fine chemicals and molecules, and are increasingly used as tools in processes as diverse as food preservation or bioremediation. Importantly, yeasts are excellent models of cell and molecular biology for higher eukaryotes, including humans, contributing with key discoveries to understand processes and diseases. All taken, yeast-related business is worth billions, critically contributing to the economical welfare of many differently developed countries. This book provides some insights into aspects of yeast science and biotechnology less frequently addressed in the literature but nonetheless decisive to improve knowledge and, accordingly, boost up yeast-based innovation.